ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA SURAKARTA TAHUN 2010 – 2014 - Dewi Saptantinah Puji Astuti, Nur Andhika Chandra Kurniawan, Fadjar Harimurti & (Universitas Slamet Riyadi, 2016)
Hotel Tax in Surakarta Mayor Regulation No. 33 by 2013 on Guidelines Implementation article 7 Hotel Tax that is defined by 10%. The purpose of this research is to know the tax realization hotel which can be charged by the Government is effective in accordance with the target set by the local government as well as knowing the magnitude of the contribution of tax revenues towards the hotel tax revenue area and PAD the city of Surakarta. Data analysis techniques used are: (1) the ratio of effectiveness describes the degree of effectiveness of the comparison between the results obtained with the achievement of the targets that have been set and (2) rasio contributions used to measure the magnitude of the amount awarded hotel tax against tax areas as well as Surakarta PAD. The results of this research are: (1) the realization of the tax revenue the tax target against hotel hotel in 2010 – 2014 proved